A scoping review of partners and in-law roles in postpartum depression - Rahayu, Lintang Kemuning Mustikaning; Shaluhiyah, Zahroh; Suryoputro, Antono (Universitas Gadjah Mada, 2025)
Purpose: Postpartum depression (PPD) affects about 17.22% of women globally, with higher rates in regions like Southern Africa and Southeast Asia, and is associated with negative impacts on breastfeeding, self-care, infant care, and maternal mental health. Support from family members plays a crucial role in protecting mothers from PPD by providing emotional and practical assistance. However, in some family arrangements, while in-laws can be supportive, conflicts or unmet expectations may also increase the risk of emotional distress and PPD. This study seeks to identify existing literature on the roles of family support in postpartum care. Methods: A scoping review was conducted using PubMed and ScienceDirect as databases, applying search terms such as “Mothers”, “Support”, and “Postpartum Depression”. Results: A total of 11 published articles between 2020 and 2025 were selected after meeting the inclusion criteria. This review emphasizes the essential role of familial relationships in shaping postpartum mental health within traditional household settings. Supportive behaviors from husbands consistently emerged as protective factors against PPD by reducing psychological stress, which can contribute to depressive symptoms. Likewise, the role of in-laws can either alleviate or intensify maternal stress. Conclusion: Husbands are encouraged to engage in open and empathetic communication with their partners, providing consistent emotional support and reassurance. Furthermore, husbands can serve a pivotal role in managing dynamics within the extended family by establishing appropriate boundaries and fostering a supportive and respectful environment that prioritizes the mother’s psychological well-being.